2023
DOI: 10.1371/journal.pone.0282487
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of tobacco use among tribal communities in India: Evidence from the first wave of Longitudinal Ageing Study in India

Abstract: Background Evidence on tobacco use among indigenous communities is scarce with available literature based either on a specific region or a particular tribe. Considering the large tribal population in India, it is pertinent to generate evidence on tobacco use among this community. Using nationally representative data, we aimed to estimate the prevalence of tobacco use and assess its determinants and regional variations among older tribal adults in India. Methods We analysed data from Longitudinal Ageing Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Tobacco consumption was assessed with the question, "Have you ever smoked tobacco (cigarette, bidi, cigar, hookah, cheroot) or used smokeless tobacco (such as chewing tobacco, gutka, pan masala, etc.)? ", the responses were dichotomous, recorded as yes or no [46].…”
Section: Predictor Variablesmentioning
confidence: 99%
“…Tobacco consumption was assessed with the question, "Have you ever smoked tobacco (cigarette, bidi, cigar, hookah, cheroot) or used smokeless tobacco (such as chewing tobacco, gutka, pan masala, etc.)? ", the responses were dichotomous, recorded as yes or no [46].…”
Section: Predictor Variablesmentioning
confidence: 99%
“…Women of the community lack knowledge of health care and the reproductive interval between two successive birth. Adequate awareness programs need to be imparted to them with proper contraceptive advice and antitobacco campaign for the tribal couples, [24,54,55,56,57].…”
Section: Gbv Among Ethenic Women In Indiamentioning
confidence: 99%
“…Due to poverty students cannot buy their school uniforms, may not establish good relationships with their peers & teachers, and hence affect their school attendance (Winny & Muchesia, 2023;Kakar et al, 2021;Lucky, 2011). However, research conducted by Kumar et al (2023) indicated that dropout rates are more prevalent among individuals from lower social and economic backgrounds. Nevertheless, different aspects such as the involvement of parents, a mother's education, teachers' attitude, sports participation, and having positive role models have been found to decrease the likelihood of dropout.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They are also more likely to live in poverty, receive public assistance, be incarcerated, and have poor health outcomes (Winny & Muchesia, 2023;Wild et al, 2023;Kishore & Shaji, 2012;Freudenberg & Ruglis, 2007;Gonzales et al, 2004). In addition, students who are dropping out from school are at higher risk of experiencing low mental health & well-being and mostly engaging in delinquent behavior (see also Kumar et al, 2023;Parreño, 2023;Liem et al, 2010;Sweeten et al, 2009). Risky behavior may also contribute to educational underachievement and increase the likelihood of dropping out (Maertens, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%